Prevalence and associated factors of dog bites: a cross-sectional study among primary school children in Madawaki District Gusau, Nigeria - Hassan, Ibrahim; Md Said, Salmiah; Ariffin, Ahmad Azuhairi; Azman, Ahmad Zaid Fattah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Dog bite is a global public health concern because it is the main risk factor for human rabies and it particularly affects children. In Nigeria, most dog bites are from stray dogs and their vaccination status remains unknown. Thus, this study aimed to investigate the prevalence and associated factors of dog bite among public primary school children in Madawaki district Gusau, Nigeria. Methods: A cross-sectional study was conducted using an unequal stratified sampling technique among 999 children aged 11 to 13-year-old at seven public primary schools from September 2017 to January 2020. A self-reported history of dog bites, socio-demographic characteristics, knowledge on interaction with dogs, knowledge on the implication of dog bites, risk behaviours of children and dog ownership were collected using a validated questionnaire. Results: The prevalence of dog bites was 54.5%. The predictors of dog bite among the children were being a male (Adjusted Odds Ratio; AOR = 2.252; Confidence Interval; CI = 1.719, 2.949), dog ownership by respondent’s family (AOR = 1.456; Cl = 1.089, 1.946), dog ownership by neighbours of the respondents (AOR = 1.752; Cl =1.334, 2.303), total score for knowledge on interaction with dogs (AOR = 0.884; Cl = 0.858, 0.911), and total score for risk behaviours of children (AOR = 1.020; Cl =1.004, 1.035). Conclusion: Poor knowledge on interaction with dogs, children’s risk behaviours around dogs, dog ownership and being male were the factors associated with a high prevalence of dog bite among primary school children from this study. These factors should be considered in order to develop an effective awareness campaign in schools to reduce the prevalence of dog bites among children.